Sistema informático para la formulación de raciones alimenticias de animales de granja para la carrera de medicina veterinaria y zootecnia del Área Agropecuaria y de Recursos Naturales Renovales. - Escudero Abad, Andrea del Carmen (2010)
The present research work is talking about the development of a computational system for feed formulation for farm animals, called SysFAG. It is based on the requirements of the School of Veterinary Medicine, and its implementation will be very useful for teachers and students. This system constitutes a tool that will allow them to elaborate a ration of minimum cost in the shortest time possible, to make a corresponding analysis of sensitivity, as well as, to maintain a historical file for each ration formulated. In addition, the system allows to enter and update information on ingredients, nutrients and nutritional requirements of animals and to generate the respective reports. Feed formulation is based on a mathematical model of linear programming. Rations are obtained at minimum cost, and solving will be made through the Two-Phases Simplex Method. This document details the results obtained during the process of developing systems following the methodology ICONIX; the system requirements in the Analysis Phase, the modelling of the use cases in the Design Phase; the characteristics of the tools used during the Construction Phase; and, the results obtained in the Tests Phase applied to the system. Finally, we present the conclusions that had been reached after completing the whole process of system development, as well as the related recommendations.